Auditory evoked response delays in children with 47, XYY syndrome. Issue 7 (1st May 2019) - Bloy, Luke; Ku, Matthew; Edgar, J. Christopher; Miller, Judith S.; Blaskey, Lisa; Ross, Judith; Roberts, Timothy P.L.
Abstract : 47, XYY syndrome (XYY) is a male sex chromosome disorder where individuals have an X chromosome and two copies of the Y chromosome. XYY is associated with a physical phenotype and carries increased risk of neurodevelopmental disorders such as autism spectrum disorder (ASD). Latencies of auditory evoked responses measured by magnetoencephalography have shown atypical prolongations in several neuropsychiatric and genetic disorders; specifically, delayed auditory responses have been observed in ASD. In this study, we investigated the associations of genotype and clinical phenotype with auditory processing. Whole cortex magnetoencephalography recorded during a passive auditory paradigm (500 Hz tones) was used to assess the auditory evoked response in three groups of male children: idiopathic ASD, typically developing, and XYY boys. Response waveforms were computed for left and right auditory cortex and latencies of the ∼50 ms (M50) and ∼100 ms (M100) components were determined. M50 latencies were significantly delayed compared with typically developing controls in children with ASD in the right hemisphere only, and in children with XYY in the left hemisphere only, irrespective of whether they met diagnostic criteria for ASD. Findings on the later M100 component trended in the same directions but did not attain significance, due to increased variance. Replicating previous findings, decreased M50 and M100 latencies with age were observed bilaterally. Overall, while XYY shares an electrophysiological phenotype (delayed evoked response latency) with idiopathic ASD, the hemispheric differences warrant further investigation.